Characteristics of injuries among elite badminton players: a systematic review - Shaharudin, M. I.; Muhamed, A. M. C.; Yusof, H. A. (Research in Sports Medicine, 2026)
Badminton is a fast-paced sport that requires a high level of skill. Despite its non-contact nature, badminton can still result in injuries. This review aimed to identify the characteristics of musculoskeletal injuries in elite badminton players. A systematic search was conducted through the electronic bibliographic databases between 2013 and 2025. The study followed the PRISMA guidelines, registered in PROSPERO, and article quality assessment was conducted using the Newcastle Ottawa Scale. A total of 11 eligible articles were included. Over 45% of elite badminton players have been injured in the past year. The most common location of injuries was at the lower extremity (54-71%), followed by the upper extremity (30-46%); tendinopathy (6-70%) and sprain (10-32%) are the most common types of injury. Identifying the characteristics of injuries in elite badminton players can provide valuable insights for healthcare professionals to develop effective injury prevention strategies for athletes.